Implementation of Model-View-ViewModel (MVVM) Architecture Pattern in the Sistem Informasi Akademik UNIDA Gontor Mobile Application - Arif, Muhammad Syakir; Musthafa, Aziz; Muriyatmoko, Dihin (Proceeding International Conference on Science and Engineering, 2020)
Software architecture primarily tuned for moderating the rising software complexities and changes. Model-View-ViewModel (MVVM) is a software architectural pattern that facilitates a separation of development of the graphical user interface from the development of the back-end logic (the data model). University of Darussalam Gontor (UNIDA Gontor) is having an Academic System called Sistem Informasi Akademik (SIAKAD) which supports the management of its college’s data administration. Currently, the SIAKAD UNIDA Gontor’s performance is still far from optimal, mainly because some of its features aren’t user-friendly yet, especially when the SIAKAD UNIDA Gontor accessed from the mobile devices. Therefore, this research aims to implement the MVVM architecture pattern in the SIAKAD UNIDA Gontor mobile application, to increase its user-friendly aspect, especially for Android device users. This research is carried out with Waterfall development method, using Kotlin programming language and utilising Android Jetpack. Results from the app testing with Black Box method show that the application is running well and have no error. Next, results from the questionnaire distributed to the users (students, lecturers and BAAK staffs) show that the application run well and satisfying. From those trial results, show that the implementation of MVVM on SIAKAD UNIDA Gontor Android application has been successful according to the scenario and ready to be applied in the even semester of 2019/2020 campus’ academic year and so on (https://play.google.com/store/apps/details?id=com.amoled.sidago). Further research and development, can be directed to the addition of new features and can support another mobile operating system, such as iOS, Tizen, Harmony OS, etc.